2003
DOI: 10.1136/sti.79.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Who is being tested for genital chlamydia in primary care?

Abstract: Objectives: To explore current patterns of testing for genital chlamydial infection in primary care, and to identify practice characteristics influencing testing rates. Method: Aggregate numbers of chlamydia tests and results for each practice in Nottingham Health District were matched to practice characteristics. Age specific testing rates and diagnosed prevalence were calculated, and characteristics of the practice tested for association with chlamydia testing rates. Results: Most tests (63.1%) were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 7 publications
3
23
2
Order By: Relevance
“…In women, younger age was associated with higher test positivity. Similar associations were shown by Dimech et al and other studies 23 24. As argued in these papers, it appears difficult to reach at-risk women below 20 for testing; possible reasons are that they do not feel at risk, be unaware of the possible implications of CT on reproductive morbidity, are more likely to refuse testing or are less likely to consult their GP.…”
Section: Discussionsupporting
confidence: 80%
“…In women, younger age was associated with higher test positivity. Similar associations were shown by Dimech et al and other studies 23 24. As argued in these papers, it appears difficult to reach at-risk women below 20 for testing; possible reasons are that they do not feel at risk, be unaware of the possible implications of CT on reproductive morbidity, are more likely to refuse testing or are less likely to consult their GP.…”
Section: Discussionsupporting
confidence: 80%
“…This may reflect the fact that the NCSP operates an opportunistic screening policy and that asymptomatic sexually active women are more likely to attend and be offered screening than men 5 . Indeed, research in primary care both before and after the introduction of the NCSP has shown that men are rarely tested for chlamydia infection 5,[14][15][16] . This may contribute to their low level of awareness of the screening programme as well as poor knowledge of chlamydia infection 13,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other studies conducted in different countries, the majority of CT tests (68.4 %) were performed in women (Kufeji et al, 2003;Hughes et al, 2007;Dimech et al, 2014;den Heijer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%